Comparative expression of lipase CAL-A in the yeasts Saccharomyces cerevisiae, Kluyveromyces lactis and Hansenula polymorpha to investigate a possible host influence - Morka, Kamila; Pietruszka, Jörg; Meyer zu Berstenhorst, Sonja (Journal of Biotechnology, 2014)
Yeasts are an attractive expression platform, as they combine the ease of handling with the eukaryotic ability to process the produced protein. Important aspects of eukaryotic protein expression are posttranslational modifications, which can be required for functional expression of the protein of interest and can only be performed by eukaryotes. Each organism has its own modification pattern: for instance, the same protein produced in different hosts is subjected to various glycosylation pathways. It is amenable that these kinds of modifications can have an influence on the biochemical properties of the protein. To verify this thesis, the well-studied lipase CAL-A from Candida antarctica was chosen as a model enzyme. The codon bias of the gene sequence was uniformly optimized and expressed in three industrially relevant yeast hosts: Saccharomyces cerevisiae, Kluyveromyces lactis, and Hansenula polymorpha. The capacity of the expression systems to produce the enzyme was analyzed, as well as the biochemical properties of the produced and purified CAL-A. All hosts produced active enzyme; however, significant differences in the obtained yield were observed. H. polymorpha appeared to be the most productive host with a tenfold increase in productivity in comparison to S. cerevisiae. Studies on thermostability and activity of the purified enzymes towards various substrates showed a significant impact of the host on the biochemical properties of the produced protein. The most thermostable CAL-A from K. lactis retained 70% of its activity after incubation at 60 °C, in comparison to 45% remaining activity for the enzyme purified from S. cerevisiae. In the screenings with different substrates, a fourfold increase in activity between the enzymes from H. polymorpha and S. cerevisiae was found. Altogether, we herein exemplify how the selection of the host even within one taxonomic family (Saccharomycetaceae) significantly affects the produced enzyme's characteristics.